Habilidades comunicativas para mejorar las relaciones interpersonales en estudiantes del segundo año de bachillerato paralelo “b”, del colegio 27 de febrero, Loja, 2017-2018. - Orellana Cueva, Gregory Santiago (2018)
The present investigation takes into account the interpersonal relationships assuming that the success that experiences in the life depends in the way in how relate us with the other people and the base of these interpersonal relations is the communication, therefore, the subject: COMMUNICATION SKILLS TO IMPROVE THE INTERPERSONAL RELATIONSHIPS IN STUDENTS OF THE SECOND YEAR OF PARALLEL "B", OF THE “27 DE FEBRERO SCHOOL”. Is proposed, whose objective sought to improve interpersonal relationships through workshops based on communication skills. It was a descriptive study of cross section, quasi-experimental design. The method used were: analytical, synthetic, deductive, inductive and statistical; The Questionnaire of interpersonal difficulties in adolescence was applied in a sample of 25 students of the second year of high school parallel "B", providing a global score and by subscales such as: the assertion, relations with the other sex, with equals, public speaking and family relationships. The results obtained from the pre-test in a general way was that 52% presented enough difficulty in interpersonal relationships, after the execution of the proposal in the post-test it was reached that in 80% they were in medium difficulty. In relation to the subscales a decrease in the degrees of difficulty was also identified. In this way, it is concluded that after the application of the intervention, the investigated adolescents who previously were in a high level of interpersonal difficulties passed to another of lower rank. For which, it reflects improvement being the proposal valid for its execution.